HOW TO BE A UX/UI DESIGNER? - Tiawan Tiawan; Noor Syam Azwar; Amar Fauzi; Annisa Zachry; Vira Virginia (Universitas Majalengka, 2021)
The Covid-19 pandemic era is not a limitation in sharing knowledge with the public, Indorama Engineering polytechnic in collaboration with Bisa Ai has created a webinar,